Gravet, C., Lievois, K. (Eds.) (2021). Vous avez dit littérature belge francophone ? Le défi de la traduction. Peter Lang. (pp. 436): Book review - Peeters, Kris (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
book review